Optimalisasi Ekspor Produk Ekonomi Kreatif Indonesia Menuju Peningkatan Dayasaing - Sugiyono Madelan (Business Economic, Communication, and Social Sciences (BECOSS) Journal, 2020)
Indonesia’s creative economy product exports have not been optimal. The purpose of this study is to optimize the goals of creative economic development in Indonesia. This research was conducted using secondary time series data for the period 2010-2017. The research method uses linear programming and goal programming. The results showed that exports of creative economy products responded to an increase in export selling prices based on the demand behavior of the exports of creative economy products. The factor of export competitiveness of Indonesia’s creative economy products lies in the use of cheaper labor costs. Exports of creative economy products do not automatically increase, if the education level of the workforce increases, but rather comes from an increase in creativity. Fashion products are efficient products compared to producing exports of craft products and culinary products. Finally, the development of the creative economy is more optimal for the purpose of increasing exports of creative economy products than for the purpose of increasing employment, namely by producing fashion products.